Performance of fiscal measures in rectifying fiscal imbalances in Saudi Arabia - Sana Naseem (Financial Studies, 2020)
This paper aims to assess the fiscal measures performance in Saudi Arabia initiated in 2016 and onwards in improving fiscal imbalances during the pre-reform period (2012-2015) and post-reform period (2016-2019). In this research, t-Test paired two samples for means has been used to determine the pre- and post-fiscal reform performance. The study finds that there is a significant difference in real gross domestic product, Debt-gross domestic product ratio and Central Government net financial assets over the two periods while fiscal deficit, current account deficit, oil prices and non-oil gross domestic product growth shows no significant difference over the two periods. Therefore, Saudi Arabian policymakers should take extensive steps to finance its budget deficit and should implement suitable policies that accelerate non-oil gross domestic product growth and meet the needs of citizens. The outcome of this research can be used in future research to perceive the impact of Vision 2030 on the Saudi economy
Keywords: E62; H62; H63; 330; Fiscal Reforms; Fiscal Deficit; Oil Prices; Real-GDP Growth; Saudi Arabia